Composite structure cable for new energy system and preparation method thereof

By employing tin-plated copper composite conductors and a multi-layer structure design in the cable, the problems of insufficient flame retardancy, water resistance, insulation aging, and mechanical properties of energy storage cables have been solved, enabling the application of high-performance new energy cables.

CN120878341APending Publication Date: 2025-10-31SHANGHAI RONDA CABLE GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511125504.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-12
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Existing energy storage cables are inadequate in terms of flame retardancy, water resistance, insulation aging resistance, and mechanical properties, and are not environmentally friendly, failing to meet the comprehensive performance requirements of new energy systems.

Method used

It adopts tin-plated copper composite conductor, and is wrapped with an insulation layer, a heat-conducting layer, a flame-retardant and water-blocking layer, a composite shielding layer and an outer sheath. Combined with silver-plated copper wire and aluminum-plastic tape corrugated tube design, it improves the cable's flame retardancy, water resistance, heat dissipation and mechanical properties.

Benefits of technology

It achieves composite structure cables that do not spread under 1000℃ flame, release no toxic gases, are resistant to high and low temperatures, have excellent mechanical properties and environmental friendliness, and are suitable for new energy systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120878341A_ABST
    Figure CN120878341A_ABST
Patent Text Reader

Abstract

The invention relates to a composite structure cable for a new energy system and a preparation method thereof. The composite structure cable is characterized in that the composite structure cable comprises a tinned copper composite conductor, and the tinned copper composite conductor is sequentially wrapped with an insulating layer, a heat conduction layer, a flame-retardant waterproof layer, a composite shielding layer and an outer sheath; the tinned copper composite conductor is composed of a tinned soft copper conductor and a plurality of silver-plated copper wires embedded in the conductor, the silver-plated copper wires form a silver-plated copper wire layer on the surface of the tinned soft copper conductor, and the composite shielding layer comprises a copper aluminum strip shielding layer and a tinned copper wire braided shielding layer. When the composite structure cable is used, the flame-retardant waterproof layer and the heat conductor are cooperated, the contradiction of flame retardance, water resistance and heat dissipation of a traditional cable is solved, the flame-retardant waterproof layer passes UL94 V-0 authentication and can bear flame combustion at 1000 DEG C for 30 minutes without spreading, the safety performance is improved, the insulation resistance retention rate is larger than or equal to 99% in the environment of-40 DEG C to 150 DEG C, and the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of cables, specifically to a composite structure cable for new energy systems and its preparation method, and more particularly to a composite structure cable suitable for connection between energy storage battery modules and its preparation method. Background Technology

[0002] With the rapid development of new energy storage systems, battery connection cables need to meet comprehensive performance requirements such as high current carrying capacity, high temperature resistance, flame retardancy, resistance to mechanical stress, and environmental protection.

[0003] In existing technologies, energy storage cables generally suffer from the following problems: 1. Insufficient flame retardant and waterproof performance: Traditional cables have a single flame retardant layer, which cannot simultaneously cope with the spread of fire and moisture penetration in complex environments.

[0004] 2. Risk of insulation aging: Ordinary insulation materials are prone to aging under high temperature or frequent charge-discharge cycles, which leads to a decline in insulation performance.

[0005] 3. Weak mechanical performance: Energy storage systems have limited installation space, and cables need to be frequently bent and subjected to pressure, making traditional structures prone to breakage.

[0006] 4. Insufficient environmental friendliness: Some materials contain halogens, which release toxic gases when burned, failing to comply with environmental regulations.

[0007] Therefore, there is an urgent need for a composite cable with comprehensive performance characteristics such as high current carrying capacity, high temperature resistance, flame retardancy, resistance to mechanical stress, and environmental friendliness, as well as its preparation method. Summary of the Invention

[0008] The purpose of this invention is to provide an improved composite structure cable for new energy systems and its manufacturing method. Through improvements in structure and process, it solves the contradiction between flame retardancy, waterproofing, and heat dissipation in traditional cables. It can withstand 1000℃ flame burning for 30 minutes without spreading, and at the same time, no toxic gas is released during combustion.

[0009] To achieve the above objectives, the technical solution of the present invention is: a composite structure cable for a new energy system, characterized in that: the composite structure cable includes a tin-plated copper composite conductor, the tin-plated copper composite conductor is sequentially wrapped with an insulation layer, a heat-conducting layer, a flame-retardant and water-blocking layer, a composite shielding layer and an outer sheath; the tin-plated copper composite conductor is composed of a tin-plated soft copper conductor and multiple silver-plated copper wires embedded inside the conductor, the silver-plated copper wires form a silver-plated copper wire layer on the surface of the tin-plated soft copper conductor, and the composite shielding layer includes a copper-aluminum tape shielding layer and a tin-plated copper wire braided shielding layer.

[0010] Preferably, the insulating layer is made of high-temperature resistant, halogen-free, low-smoke irradiation cross-linked polyolefin material with a thickness of 0.8-1.8 mm, and is cross-linked by electron beam irradiation at a dose of 15-20 Mrad.

[0011] Furthermore, the flame-retardant and water-blocking layer is made of cross-linked polyethylene (XLPE) and inorganic minerals in a mass ratio of 6:4. After being extruded by an extruder, it is coated with an insulating layer. The inorganic minerals are magnesium hydroxide or mica powder. A heat-conducting layer is set inside the flame-retardant and water-blocking layer. The heat-conducting layer is made of a 0.15mm thick aluminum-plastic corrugated pipe.

[0012] Furthermore, the cross-section of the copper conductor in the tin-plated soft copper conductor is 4-240 mm², and the thickness of the tin plating layer on the surface of the copper conductor is ≥5 μm.

[0013] Furthermore, the outer sheath is made of low-smoke halogen-free polyurethane material LSZH-TPU, with a thickness of 1.5-2.5mm.

[0014] A method for preparing a composite structure cable for a new energy system, characterized by the following steps: a) using tin-plated soft copper wire stranded into a conductor with a cross-section of 4-240 mm², and simultaneously embedding silver-plated copper wire inside the conductor to form a silver-plated copper wire braided layer on the conductor surface, resulting in a DC resistance ≤0.01724 Ω·km; b) extruding an insulation layer onto the silver-plated copper wire braided layer, the insulation layer being made of a high-temperature resistant, halogen-free, low-smoke radiation-crosslinked polyolefin material with a thickness of 0.8-1.8 mm. Electron beam irradiation at a dose of 15-20 Mrad is used to crosslink the high-temperature resistant, halogen-free, low-smoke irradiation crosslinked polyolefin material to improve its temperature resistance; c) A flame-retardant and water-blocking layer and a thermally conductive layer are extruded onto the surface of the insulation layer using an extruder. The flame-retardant and water-blocking layer is made of crosslinked polyethylene (XLPE) and inorganic minerals in a mass percentage ratio of 6:4; d) A copper-aluminum strip shielding layer and a tin-plated copper wire braided shielding layer are sequentially wrapped around the surface of the flame-retardant and water-blocking layer to form a composite shielding layer; e) An outer sheath made of low-smoke, halogen-free polyurethane material is wrapped around the surface of the composite shielding layer.

[0015] Preferably, in step a, the thickness of the tin plating layer on the surface of the tin-plated soft copper conductor is ≥5μm.

[0016] Furthermore, in step c, the inorganic mineral is magnesium hydroxide or mica powder. After the cross-linked polyethylene is mixed with the inorganic mineral, it is extruded through an extruder at a temperature controlled at 120-140℃, and the resulting flame-retardant and water-blocking layer has a water absorption rate of ≤0.1%.

[0017] Furthermore, in step c, a heat-conducting layer is provided inside the flame-retardant and water-blocking layer. The heat-conducting layer is made of aluminum-plastic corrugated pipe with a longitudinal thickness of 0.15mm to achieve a longitudinal water-blocking effect.

[0018] Compared with the prior art, the technical solution of the present invention not only improves the overall technical solution, but also includes many improvements in details. Specifically, it has the following beneficial effects: 1. The improved solution of the present invention, wherein the composite structure cable includes a tin-plated copper composite conductor, and the tin-plated copper composite conductor is wrapped with an insulation layer, a heat-conducting layer, a flame-retardant and water-blocking layer, a composite shielding layer and an outer sheath in sequence. The flame-retardant and water-blocking layer works in conjunction with the heat conductor to solve the contradiction between flame retardancy, waterproofing and heat dissipation in traditional cables. The flame-retardant and water-blocking layer has passed UL94 V-0 certification and can withstand 1000℃ flame burning for 30 minutes without spreading, which improves safety performance. In an environment of -40℃~150℃, the insulation resistance retention rate is ≥99%, which extends the service life. 2. In the technical solution of the present invention, the tin-plated copper composite conductor is composed of a tin-plated soft copper conductor and multiple silver-plated copper wires embedded inside the conductor. The silver-plated copper wires form a silver-plated copper wire layer on the surface of the tin-plated soft copper conductor, which improves the oxidation resistance and welding performance, while enhancing the flexibility and adapting to the laying in narrow spaces. 3. In the technical solution of the present invention, the flame-retardant and water-blocking layer is made of cross-linked polyethylene XLPE and inorganic minerals mixed in a mass percentage ratio of 6:4. After being extruded by an extruder, it is coated with an insulating layer, so that the flame-retardant and water-blocking layer has both flame-retardant (UL94 V-0 rating) and waterproof (water absorption rate ≤0.1%) functions. A heat-conducting layer is provided inside the flame-retardant and water-blocking layer. The heat-conducting layer is made of aluminum-plastic corrugated pipe with a longitudinal thickness of 0.15mm, which can realize cable heat dissipation and at the same time has longitudinal water-blocking function. 4. The composite structure cable prepared in this invention has high and low temperature resistance. It has passed the high and low temperature cycle test of -50℃ to 125℃ and the rigorous low temperature winding (-50℃) and low temperature impact (-50℃) test, and has good low temperature toughness. At the same time, it has excellent wear resistance; tensile strength ≥15Mpa and tear strength ≥40N, making it more suitable for high-requirement cable applications in the military and aerospace fields. 5. The preparation technology of the present invention has simple process steps, is easy to implement, and is easy to promote and utilize. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the structure of the present invention.

[0020] Figure label: 1. Tin-plated soft copper conductor, 2. Silver-plated copper wire layer, 3. Insulation layer, 4. Thermally conductive layer, 5. Flame-retardant and water-blocking layer, 6. Outer sheath, 7. Copper-aluminum strip shielding layer, 8. Tin-plated copper wire braided shielding layer. Detailed Implementation

[0021] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] This invention provides a composite structure cable for new energy systems, see details below. Figure 1 The difference between this and the existing technology is that the composite structure cable includes a tin-plated copper composite conductor, and the tin-plated copper composite conductor is wrapped with an insulation layer 3, a heat-conducting layer 4, a flame-retardant and water-blocking layer 5, a composite shielding layer and an outer sheath 6 in sequence; the tin-plated copper composite conductor is composed of a tin-plated soft copper conductor 1 and multiple silver-plated copper wires embedded inside the conductor, and the silver-plated copper wires form a silver-plated copper wire layer 2 on the surface of the tin-plated soft copper conductor; the composite shielding layer includes a copper-aluminum tape shielding layer 7 and a tin-plated copper wire braided shielding layer 8.

[0023] When in use, the composite structure cable uses a flame-retardant and water-blocking layer in conjunction with a heat conductor to solve the contradiction between flame retardancy, waterproofing and heat dissipation in traditional cables. The flame-retardant and water-blocking layer is UL94 V-0 certified and can withstand 1000℃ flame burning for 30 minutes without spreading, which improves safety performance. In an environment of -40℃~150℃, the insulation resistance retention rate is ≥99%, which extends the service life.

[0024] Example 1 This embodiment describes a composite structure cable for a new energy system; see details below. Figure 1 The difference between this and the existing technology is that the composite structure cable includes a tin-plated copper composite conductor, and the tin-plated copper composite conductor is wrapped with an insulation layer 3, a heat-conducting layer 4, a flame-retardant and water-blocking layer 5, a composite shielding layer and an outer sheath 6 in sequence; the tin-plated copper composite conductor is composed of a tin-plated soft copper conductor 1 and multiple silver-plated copper wires embedded inside the conductor, and the silver-plated copper wires form a silver-plated copper wire layer 2 on the surface of the tin-plated soft copper conductor; the composite shielding layer includes a copper-aluminum tape shielding layer 7 and a tin-plated copper wire braided shielding layer 8.

[0025] The surface of the tin-plated copper wire braided shielding layer is provided with evenly distributed raised nickel alloy silicon steel sheets. The thickness of the nickel alloy silicon steel sheets is 0.4-0.6mm, and the shape is triangular or star-shaped, which plays a role in good insulation and shielding and further effective heat dissipation.

[0026] Specifically, the insulation layer is made of high-temperature resistant, halogen-free, low-smoke irradiation cross-linked polyolefin material with a thickness of 0.8-1.8 mm, preferably 1.2-1.5 mm. The high-temperature resistant, halogen-free, low-smoke irradiation cross-linked polyolefin material is cross-linked by electron beam irradiation at a dose of 15-20 Mrad, which can prevent insulation aging.

[0027] Furthermore, the flame-retardant and water-blocking layer is made by mixing cross-linked polyethylene (XLPE) and inorganic minerals in a mass ratio of 6:4, extruding the mixture through an extruder, and then coating it with an insulating layer. The inorganic minerals used are magnesium hydroxide or mica powder. The flame-retardant and water-blocking layer has both flame-retardant (UL94 V-0 rating) and waterproof functions, with a water absorption rate of ≤0.1%.

[0028] A heat-conducting layer 4 is installed inside the flame-retardant and water-blocking layer 5. The heat-conducting layer is made of a 0.15mm thick aluminum-plastic corrugated strip. The surface of the aluminum-plastic strip has raised star-shaped or triangular heat conductors made of copper or aluminum, which can solve the cable heat dissipation problem and also have a longitudinal water-blocking function. Furthermore, a layer of fire-retardant silicone cloth is attached to the surface of the aluminum-plastic strip. This waterproof and flame-retardant silicone cloth has holes corresponding to the heat conductors, so that the heat conductors protrude from the waterproof and flame-retardant silicone cloth by 0.2-0.6mm, which not only achieves better waterproof and flame-retardant effect, but also has good heat dissipation performance.

[0029] Furthermore, the cross-sectional area of ​​the tin-plated soft copper conductor is 4-240 mm², and the tin plating layer thickness on the surface of the copper conductor is ≥5 μm. The tin-plated copper composite conductor consists of a tin-plated soft copper conductor and multiple silver-plated copper wires embedded inside the conductor. The diameter of the silver-plated copper wires is 0.04-0.08 mm. The silver-plated copper wires form a silver-plated copper wire layer on the surface of the tin-plated soft copper conductor with a thickness of 0.2-0.8 mm, which improves oxidation resistance and solderability, while also enhancing flexibility and adapting to installation in confined spaces. During embedding, 3-5 silver-plated copper wires are grouped together and inserted into the copper conductor at a 20-45 degree angle to the conductor's centerline in a clockwise direction. After inserting one circle around the circumference of the copper conductor, another 3-5 silver-plated copper wires are grouped together and inserted into the copper conductor at a 20-45 degree angle to the conductor's centerline in a counterclockwise direction. The copper conductor here is made of tin-plated soft copper wire twisted together, and the silver-plated copper wires are inserted during the twisting process.

[0030] Furthermore, the outer sheath is made of low-smoke halogen-free polyurethane material LSZH-TPU, with a thickness of 1.5-2.5mm. This significantly improves upon the problem that traditional halogen-free flame-retardant TPU cannot meet testing requirements for smoke density and light transmittance in cable sheath applications.

[0031] The composite structure cable for a new energy system in this embodiment has the following advantages: a. High and low temperature resistance: Supports finished cables to pass high and low temperature cycle tests of -50℃ to 125℃ and strict low temperature winding (-50℃) and low temperature impact (-50℃) tests; good low temperature toughness.

[0032] b. Excellent wear resistance: As a polar material, it has high bonding energy and wear resistance far superior to traditional low-smoke halogen-free polyolefin materials (LSZH).

[0033] c. High mechanical properties: Tensile strength (≥15Mpa), tear strength (≥40N) and elastic modulus are all far superior to traditional low smoke halogen-free polyolefin (LSZH), making it more suitable for high-requirement cable applications in the military and aerospace fields.

[0034] d. Hydrolysis resistance: The cable is supported to pass the 1000 / 2000Hrs hydrolysis resistance test (85℃ / 85%RH, 1000 / 2000Hrs).

[0035] It can be widely used for connecting energy storage battery modules (such as containerized energy storage systems), high-voltage DC transmission in photovoltaic / wind power energy storage systems, or frequently moved energy storage devices (such as mobile energy storage power stations). It has broad application prospects and is easy to promote and utilize.

[0036] Example 2 This embodiment describes a method for preparing a composite structure cable for a new energy system, which differs from existing technologies in that the preparation method includes the following steps: a) using tin-plated soft copper wire stranded into a conductor with a cross-section of 4-240 mm², and embedding silver-plated copper wire inside the conductor to form a silver-plated copper wire braided layer on the conductor surface, resulting in a DC resistance ≤0.01724 Ω·km; b) extruding an insulation layer onto the silver-plated copper wire braided layer. The insulation layer is made of high-temperature resistant, halogen-free, low-smoke radiation-crosslinked polyolefin material with a thickness of 0. The high-temperature resistant, halogen-free, low-smoke irradiation crosslinked polyolefin material is crosslinked with electron beam irradiation at a dose of 15-20 Mrad to improve its temperature resistance; c) a flame-retardant and water-blocking layer and a thermally conductive layer are extruded onto the surface of the insulation layer using an extruder. The flame-retardant and water-blocking layer is made of crosslinked polyethylene (XLPE) and inorganic minerals in a mass percentage ratio of 6:4; d) a copper-aluminum strip shielding layer and a tin-plated copper wire braided shielding layer are sequentially wrapped around the surface of the flame-retardant and water-blocking layer to form a composite shielding layer; e) an outer sheath made of low-smoke, halogen-free polyurethane material is wrapped around the surface of the composite shielding layer.

[0037] Preferably, in step a, the thickness of the tin plating layer on the surface of the tin-plated soft copper conductor is ≥5μm.

[0038] Furthermore, in step c, the inorganic mineral is magnesium hydroxide or mica powder. After the cross-linked polyethylene is mixed with the inorganic mineral, it is extruded through an extruder at a temperature controlled at 120-140℃, and the resulting flame-retardant and water-blocking layer has a water absorption rate of ≤0.1%.

[0039] The extrusion process is carried out in two steps. First, a spiral extrusion is performed around the conductor surface in a clockwise direction to form a spiral insulating strip on the conductor surface. There are gaps between the connected insulating strips, with a gap size of 3-8mm, forming an insulating cavity. The second step is to perform a second full-coverage extrusion on the conductor surface.

[0040] Furthermore, in step c, a heat-conducting layer is provided inside the flame-retardant and water-blocking layer. The heat-conducting layer is made of aluminum-plastic corrugated pipe with a longitudinal thickness of 0.15mm to achieve a longitudinal water-blocking effect.

[0041] This invention employs a flame-retardant and water-blocking layer in synergy with a heat conductor to resolve the inherent contradictions between flame retardancy, waterproofing, and heat dissipation in traditional cables. Simultaneously, the halogen-free, low-smoke insulation layer and PTFE sheath comply with RoHS standards, releasing no toxic gases during combustion. The silver-plated copper wire braided layer and star-shaped heat conductor enhance mechanical flexibility and thermal management efficiency.

[0042] The beneficial effects of this invention are as follows: Enhanced safety: The flame-retardant and water-resistant layer is UL94 V-0 certified and can withstand 1000℃ flame burning for 30 minutes without spreading.

[0043] Extended lifespan: In an environment of -40℃ to 150℃, the insulation resistance retention rate is ≥99% (IEC 60502 standard).

[0044] Environmental compliance: RoHS 2.0 certified, halogen content ≤900ppm.

[0045] The above description, in conjunction with specific preferred embodiments, provides a further detailed explanation of the present invention. It should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, various simple deductions or substitutions can be made without departing from the concept of the present invention, and all such modifications and substitutions should be considered within the scope of protection of the present invention.

Claims

1. A composite structure cable for new energy systems, characterized in that: The composite structure cable includes a tin-plated copper composite conductor, which is wrapped with an insulation layer, a thermally conductive layer, a flame-retardant and water-blocking layer, a composite shielding layer, and an outer sheath in sequence. The tin-plated copper composite conductor is composed of a tin-plated soft copper conductor and multiple silver-plated copper wires embedded inside the conductor. The silver-plated copper wires form a silver-plated copper wire layer on the surface of the tin-plated soft copper conductor. The composite shielding layer includes a copper-aluminum tape shielding layer and a tin-plated copper wire braided shielding layer.

2. The composite structure cable for a new energy system according to claim 1, characterized in that: The insulation layer is made of high-temperature resistant, halogen-free, low-smoke irradiation cross-linked polyolefin material with a thickness of 0.8-1.8 mm. It is cross-linked by electron beam irradiation at a dose of 15-20 Mrad.

3. A composite structure cable for a new energy system according to claim 1, characterized in that: The flame-retardant and water-blocking layer is made of cross-linked polyethylene (XLPE) and inorganic minerals in a mass ratio of 6:

4. After being extruded by an extruder, it is coated with an insulating layer. The inorganic minerals are magnesium hydroxide or mica powder. A heat-conducting layer is set inside the flame-retardant and water-blocking layer. The heat-conducting layer is made of aluminum-plastic corrugated pipe with a longitudinal thickness of 0.15mm.

4. A composite structure cable for a new energy system according to claim 1, characterized in that: The cross-section of the copper conductor in the tin-plated soft copper conductor is 4-240 mm², and the thickness of the tin plating layer on the surface of the copper conductor is ≥5 μm.

5. A composite structure cable for a new energy system according to claim 1, characterized in that: The outer sheath is made of low-smoke halogen-free polyurethane material LSZH-TPU, with a thickness of 1.5-2.5mm.

6. The method for preparing a composite structure cable for a new energy system according to claim 1, characterized in that: The preparation method includes the following steps: a) using tin-plated soft copper wire stranded into a conductor with a cross-section of 4-240 mm², and embedding silver-plated copper wire inside the conductor to form a silver-plated copper wire braided layer on the conductor surface, so that the DC resistance is ≤0.01724 Ω·km; b) extruding an insulation layer onto the silver-plated copper wire braided layer. The insulation layer is made of high-temperature resistant halogen-free low-smoke irradiation cross-linked polyolefin material with a thickness of 0.8-1.8 mm, and cross-linking the high-temperature resistant halogen-free low-smoke irradiation cross-linked polyolefin material with an electron beam irradiation dose of 15-20 Mrad to improve the temperature resistance; c) extruding a flame-retardant and water-blocking layer and a thermally conductive layer onto the surface of the insulation layer using an extruder. The flame-retardant and water-blocking layer is made of cross-linked polyethylene XLPE and inorganic minerals mixed in a mass percentage ratio of 6:4; d) sequentially wrapping a copper-aluminum strip shielding layer and a tin-plated copper wire braided shielding layer around the surface of the flame-retardant and water-blocking layer to form a composite shielding layer. e. Cover the surface of the composite shielding layer with an outer sheath made of low-smoke halogen-free polyurethane material.

7. The method for preparing a composite structure cable for a new energy system according to claim 6, characterized in that: In step a, the thickness of the tin plating layer on the surface of the tin-plated soft copper conductor is ≥5μm.

8. The method for preparing a composite structure cable for a new energy system according to claim 6, characterized in that: In step c, the inorganic minerals used are magnesium hydroxide or mica powder. After the cross-linked polyethylene is mixed with the inorganic minerals, it is extruded through an extruder at a temperature controlled at 120-140℃. The resulting flame-retardant and water-blocking layer has a water absorption rate of ≤0.1%.

9. The method for preparing a composite structure cable for a new energy system according to claim 6, characterized in that: In step c, a heat-conducting layer is set inside the flame-retardant and water-blocking layer. The heat-conducting layer is made of aluminum-plastic corrugated pipe with a longitudinal thickness of 0.15mm to achieve longitudinal water-blocking effect.